2018
DOI: 10.1002/hep4.1253
|View full text |Cite
|
Sign up to set email alerts
|

Niacin‐Induced Anicteric Microvesicular Steatotic Acute Liver Failure

Abstract: Niacin (vitamin B3) is available as a prescription medication and over‐the‐counter supplement. Although it is well known for its vasodilatory effect, it has also been associated with mild hepatotoxicity and, rarely, acute liver failure. We present the case of a 74‐year‐old Hispanic woman who developed acute liver failure (anicteric encephalopathy and coagulopathy) after her home dose of immediate‐release niacin was replaced with an extended‐release formulation during an inpatient hospital stay. This is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Excessive vitamin B3 intake could provoke flushing, headaches, light-headedness, itching, nausea and vomiting. In addition, liver injury can occur in rare cases and progress to fulminant hepatic failure 49 . As the indiscriminate use of vitamin and mineral supplements may adversely affect physiological function and impair health 50 , it is recommended to consume high nutrient density food rather than nutritional supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive vitamin B3 intake could provoke flushing, headaches, light-headedness, itching, nausea and vomiting. In addition, liver injury can occur in rare cases and progress to fulminant hepatic failure 49 . As the indiscriminate use of vitamin and mineral supplements may adversely affect physiological function and impair health 50 , it is recommended to consume high nutrient density food rather than nutritional supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive vitamin B3 intake could provoke ushing, headaches, light-headedness, itching, nausea and vomiting. In addition, liver injury can occur in rare cases and progress to fulminant hepatic failure 39 . As the indiscriminate use of vitamin and mineral supplements may adversely affect physiological function and impair health 40 , it is recommended to consume high nutrient density food rather than nutritional supplements.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NA had no impact on diet-induced NAFLD development in C57BL/6J mice but potentiated hepatic steatosis in HFD-fed B6129SF2/J mice ( Fang et al., 2020 ). Additionally, NA usually causes liver toxicity at doses higher than 3 g/day, which may be caused by mitochondrial damage ( Leung et al., 2018 ). The most obvious known side effect of NA administration is flushing, which is caused by the production of prostaglandins D2 and E2 by subcutaneous Langerhans cells through GPR109A ( Kamanna and Kashyap, 2008 ).…”
Section: Strategies To Boost Nad + and Its Effect ...mentioning
confidence: 99%